Hostel. Part II - Roth, Eli; Fleiss, Mike; Briggs, Chris (Liongate; distributed in the Philippines by MagnaVision, 2007)
Set in and around a Slovakian factory, European students are kidnapped, tortured, and killed by rich businessmen who pay enormous amounts of money to experience death firsthand. All tattooed with a bulldog insignia, an international elite bid on young people to slaughter in a trade catering to those with a death fetish. Three girls, Beth, Whitney, and Lorna, are lured to Slovakia by a sultry European woman. Sidetracked and disoriented, the girls slip away one by one.